Effects of Response Option Order on Likert-Type Psychometric Properties and Reactions. (December 2022) - Robie, Chet; Meade, Adam W.; Risavy, Stephen D.; Rasheed, Sabah
The effects of different response option orders on survey responses have been studied extensively. The typical research design involves examining the differences in response characteristics between conditions with the same item stems and response option orders that differ in valence—either incrementally arranged (e.g., strongly disagree to strongly agree) or decrementally arranged (e.g., strongly agree to strongly disagree). The present study added two additional experimental conditions—randomly incremental or decremental and completely randomized. All items were presented in an item-by-item format. We also extended previous studies by including an examination of response option order effects on: careless responding, correlations between focal predictors and criteria, and participant reactions, all the while controlling for false discovery rate and focusing on the size of effects. In a sample of 1, 198 university students, we found little to no response option order effects on a recognized personality assessment vis-à-vis measurement equivalence, scale mean differences, item-level distributions, or participant reactions. However, the completely randomized response option order condition differed on several careless responding indices suggesting avenues for future research.